Making it personal: Opportunity individuation and the shaping of opportunity beliefs - Wood, Matthew S.; McKelvie, Alexander; Haynie, J. Michael (Journal of Business Venturing, 2014)
We develop a model that focuses on the individuation of opportunity beliefs. We adopt inferences from the ecology literature and integrate those with mental model theory to examine the ‘individuation’ of opportunity as the result of the interplay between industry conditions and person-specific factors. We test our predictions using conjoint analysis of 2880 opportunity decisions. We find that an entrepreneur's related knowledge, motivation to evaluate the opportunity, prior failure, and fear of failure shape perceptions of opportunity attractiveness as one individuates exogenous opportunity information. We articulate our findings as evidence that when combined with opportunity related data, an individual's cognitive resources play an important role as one forms opportunity beliefs about the personal attractiveness of pursing an opportunity.